2010
DOI: 10.1111/j.1748-0361.2010.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Midwestern Rural Adolescents’ Anal Intercourse Experience

Abstract: Anal sexual activity is a component of some rural adolescents' sexual experiences. These findings have important implications for sex education programs targeted to rural schools, where the typical high school classroom may have some students engaging in anal sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…With these points, such sexual encounters (unprotected) increase the vulnerability to HIV/AIDS and STIs. Another study has also shown that not using condoms in anal sex is the riskiest action with regards to being infected by HIV ( 21 ). Based on the results of the study, although male participants were aware of HIV risk at a cognitive level, they had limited knowledge about various sexual modes of HIV and STIs transmission.…”
Section: Discussionmentioning
confidence: 99%
“…With these points, such sexual encounters (unprotected) increase the vulnerability to HIV/AIDS and STIs. Another study has also shown that not using condoms in anal sex is the riskiest action with regards to being infected by HIV ( 21 ). Based on the results of the study, although male participants were aware of HIV risk at a cognitive level, they had limited knowledge about various sexual modes of HIV and STIs transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Youth Risk Behavior Survey have consistently shown that nearly half of high school‐aged youth are sexually active and less than two thirds of those reported using a condom at last intercourse. In addition, a significant portion of adolescents put themselves at risk by engaging in other high‐risk sexual behaviors such as oral (39%) and anal sex (7% to 20% of boys and 3% to 41% of girls) 5,6 . Only 87% of high school students reported having learned about HIV/AIDS in school in the 2009 survey, representing the lowest percentage since 1997 7–10 …”
mentioning
confidence: 99%
“…Most of these relied on community engagement for successful recruitment of research participants. Involvement of community personnel (n = 46) [ 17 62 ], feedback (n = 22) [ 18 , 20 , 23 , 25 , 26 , 31 , 32 , 34 , 38 , 42 45 , 49 , 51 53 , 55 57 , 61 , 62 ], and customization of recruitment materials and processes in accordance with the characteristics of the community (n = 17) [ 19 , 22 , 25 27 , 32 , 34 , 45 , 47 50 , 52 , 56 , 58 , 61 , 63 ] were mentioned most frequently. Some other recruitment strategies included providing remuneration (either for participants or for community personnel) (n = 14) [ 19 , 23 , 31 , 33 , 35 , 37 , 42 , 44 , 48 , 49 , 51 , 54 , 58 , 61 ] and utilizing local spaces and events (n = 15) [ 19 , 21 , 22 , 28 30 , 38 , 39 , 42 , 46 , 56 , 58 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Involvement was identified as the level of engagement in half of the studies (n = 24) [ 17 , 19 , 21 , 22 , 26 , 28 30 , 32 , 33 , 36 , 38 , 39 , 45 , 47 , 48 , 55 61 , 63 ]. In most of these studies, the research teams developed partnerships with local organizations or recruited community personnel and liaisons.…”
Section: Resultsmentioning
confidence: 99%